Forest exploitation for charcoal production and timber since the 12th century in an intact medieval mining site in the Niederpöbel Valley (Erzgebirge, Eastern Germany). (December 2015) - Tolksdorf, Johann Friedrich; Elburg, Rengert; Schröder, Frank; Knapp, Hannes; Herbig, Christoph; Westphal, Thorsten; Schneider, Birgit; Fülling, Alexander; Hemker, Christiane
Abstract: Historic mining activities are assumed to rank among the most significant human activities that reshaped the landscape of the European uplands, especially since the medieval period. Mining requires both the extraction of timber for mining construction as well as the production of charcoal for ore smelting. Analysing the occurrence of different wood taxa in construction or charcoal assemblages may help to shed light on the question of whether different taxa had been chosen for different purposes depending on their local availability, specific cost–benefit considerations or their physical properties. Here, we present the results of taxonomical and dendrochronological analyses performed on timber and macro-remains from an outstandingly well-preserved medieval underground mining complex in the Erzgebirge region (Ore Mountains, Eastern Germany). The complementary use of wood for charcoal production was reconstructed by anthracological and chronological analyses of medieval to modern charcoal kilns preserved in the same area. Dated colluvial layers served as additional indicators for phases of local soil erosion following forest clearances. The onset of mining activities in the late 12th century was contemporary with the start of charcoal production and soil erosion. While Abies alba was prevalent among the timbers from the main construction phase around AD 1270/1280, Fagus sylvatica was the most frequently occurring wood in the oldest charcoal kilns from the mid-13th century. The latter declined during the 13th century in favour of taxa like Betula, Corylus and Acer . Supported by the evidence of massive soil erosion, this may reflect changes in forest composition induced by highly intensive use or shifts of the areas used for wood exploitation. Whereas mining ceased in the area shortly after AD 1291, charcoal production continued during the 14th and 15th century and the rising proportion of Abies alba is discussed to be related to a lessened local demand of this species for timber. The rising share of Picea during the younger phases probably resulted from changes in selective forest exploitation rather than mirroring vegetation changes. After a hiatus, a last phase of charcoal production is identified to have occurred during the mid-16th century, again with a high share of Fagus sylvatica as fuel wood. Highlights: Preserved mining features and charcoal kilns from the 12th/13th century. Onset of mining activities accompanied by soil erosion. Very selective use of Abies alba for timbering the mines. Broad range of taxa used for charcoal production. Indication for highly selective use of wood.